Patients’ Attitude toward Breaking Bad News; a Brief Report - Aminiahidashti, Hamed; Mousavi, Seyed Jaber; Darzi, Mohammad Mehdi (Archives of Academic Emergency Medicine, 2018)
Introduction: Delivering bad news is a stressful moment for both physicians and patients. The purpose of this investigation was to explore the patients’ preferences and attitudes toward being informed about the bad news. Methods: This cross-sectional study was done on patients admitted to Imam Khomeini Hospital, Sari, Iran, from September 2014 to February 2015. Patient attitude regarding breaking bad news was evaluated using a reliable and valid questionnaire. Results: 130 patients were evaluated (61.5% male, mean age = 46.21 ± 12.1 years). 118 (90.76%) participants believed that the patient himself/herself should be informed about the disease’s condition. 120 (92.30%) preferred to hear the news from a skillful physician and 105 (80.76%) believed that emergency department is not a proper place for breaking bad news. Conclusion: Based on the results of the present study, most participants believed that the most experienced and skillful physician should inform them completely regarding their medical condition. At the same time they declared that, it is best to hear bad news in a calm and suitable place and time rather than emergency department or hospital corridors during teaching rounds.